Maternal periodontal disease and preterm birth: A case-control study - Pushpalatha Govindaraju; Sanjay Venugopal; Madhura Antharasanahalli Shivakumar; Shruthi Sethuraman; Santhosh Kumar Ramaiah; Sowmya Mukundan (Wolters Kluwer Medknow Publications, 2015)
Background and Objective: Preterm birth (PTB) is an important issue in public health and is a major cause for infant mortality and morbidity. There is a growing consensus that systemic diseases elsewhere in the body may influence PTB. Recent studies have hypothesized that maternal periodontitis could be a high-risk factor for PTB. The aim of the present study was to investigate the relationship between maternal periodontitis on PTB. Materials and Methods: Forty systemically healthy primiparous mothers aged 18-35 years were recruited for the study. Based on inclusion and exclusion criteria, they were categorized into PTB group as cases and full term birth group (FTB) as controls. PTB cases (n = 20) defined as spontaneous delivery before/<37 completed weeks of gestation. Controls (FTB) were normal births at or after 37 weeks of gestation. Data on periodontal status, pregnancy outcome variables, and information on other factors that may influence adverse pregnancy outcomes were collected within 2 days of labor. Data were subjected to Student's t-test and Pearson's correlation coefficient statistical analysis. Results: Statistically significant difference with respect to the gestational period at the time of delivery and birth weight of the infants in (PTB) group (<0.001) compared to (FTB) group was observed. Overall, there was statistically significant poor periodontal status in the (PTB) group compared to (FTB) group. The statistical results also showed a positive correlation between gestational age and clinical parameters. Conclusion: An observable relationship was noticed between periodontitis and gestational age, and a positive correlation was found with respect to PTB and periodontitis. Further studies should be designed to establish periodontal disease as an independent risk factor for PTB/preterm low birth weight.